Numerical Investigations and Optimized Design of the Active Cooling Performance with Phase Change for Aircraft Rudder Shaft - Xiangchun Sun; Kaiyan Jin; Kuan Zhao; Hexuan Zhang; Guice Yao; Dongsheng Wen (Applied Sciences)
During hypersonic flight, the air rudder shaft can undergo huge aerodynamic heating load, where it is necessary to design the thermal protection system of the air rudder shaft. Aiming to prevent the rudder shaft from thermal failure due to the heat endurance limit of materials, numerical investigations are conducted systemically to predict the active cooling performance of the rudder shaft with liquid water considering phase change. The validation of the numerical simulation method considering phase-change heat transfer is further investigated by experiments. The effect of coolant injection flow velocity on the active cooling performance is further analyzed for both the steady state and transient state. Finally, to achieve better cooling performance, an optimized design of the cooling channels is performed in this work. The results of the transient numerical simulation show that, employing the initial cooling structures, it may undergo the heat transfer deterioration phenomenon under the coolant injection velocity below 0.2 m/s. For the rudder shaft with an optimized structure, the heat transfer deterioration can be significantly reduced, which significantly reduces the risk of thermal failure. Moreover, the total pressure drop of the optimized rudder shaft under the same coolant injection condition can be reduced by about 19% compared with the initial structure. This study provides a valuable contribution to the thermal protection performance for the rudder shaft, as a key component of aircraft under the aero heating process.